(untitled) (Revista Nacional de Odontología, 2014)
Introduction: the purpose of this research was to determine oral morbidity in the subsidized population of Manizales served through the teaching-service model at a university clinic. Materials and methods: the descriptive study looked at a study population of 122 patients of all ages affiliated with the subsidized system. Sociodemographic, systemic precedents and oral alterations were analyzed, such as changes in the dental, gingival and periodontal surfaces, occlusion, pulp, periapical bones, joints, dental structure, dental fracture, rest of the root, alveolitis, cellulitis and dental fluorosis. Results: women made up the majority of those using the service, 62.2% (76 patients); the population showing greatest adherence was between the ages of 15 and 44, accounting for 64.7% (79 patients); the five leading causes of oral morbidity were dentine cavities, diseases originating in the pulp, periodontal disease, tmj disorder and retained dental root. Only three patients were older than 60 and their most common diagnoses were periodontal alterations. The highest cop frequency was 17.7 and involved the 60 or over age group. Conclusions: cavities and periodontal disease continue to be the most prevalent diagnoses in dental practice.